2019
DOI: 10.2196/13508
|View full text |Cite
|
Sign up to set email alerts
|

Process Evaluation of a Medical Student–Delivered Smoking Prevention Program for Secondary Schools: Protocol for the Education Against Tobacco Cluster Randomized Trial

Abstract: Background Most smokers start smoking during their early adolescence under the impression that smoking entails positive attributes. Given the addictive nature of cigarettes, however, many of them might end up as long-term smokers and suffering from tobacco-related diseases. To prevent tobacco use among adolescents, the large international medical students’ network Education Against Tobacco (EAT) educates more than 40,000 secondary school students per year in the classroom setting, using evidence-b… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…Moreover, those delivering a tobacco prevention programmes to educators and/or students are encouraged to use evidence-based educational resources, such as the Stanford Tobacco Prevention Toolkit (Stanford Medicine, 2020), a resource not used for the present study. In prior studies, medical students have delivered tobacco prevention educational classes to middle and high school students (Brinker et al, 2019), but this may not be feasible for rural communities, especially those that are medically underserved. Feasible options for rural schools may include mobile or text messaging-based tobacco education and prevention programmes for students, parents and/or educators, as used for other health behaviours in rural youth populations (Brown et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, those delivering a tobacco prevention programmes to educators and/or students are encouraged to use evidence-based educational resources, such as the Stanford Tobacco Prevention Toolkit (Stanford Medicine, 2020), a resource not used for the present study. In prior studies, medical students have delivered tobacco prevention educational classes to middle and high school students (Brinker et al, 2019), but this may not be feasible for rural communities, especially those that are medically underserved. Feasible options for rural schools may include mobile or text messaging-based tobacco education and prevention programmes for students, parents and/or educators, as used for other health behaviours in rural youth populations (Brown et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Beyond policy-level approaches, alternative strategies to tobacco prevention have included school-based education delivered to students (Brinker et al, 2019; Little et al, 2015; Nagler and Lobo, 2019; St Germain et al, 2017) and mass public health campaigns, such as The Real Cost (Brubach, 2019). Given research suggests young people believe e-cigarettes to be less harmful and less addictive than combustible cigarettes, a belief found to influence ever and past 30-day use of e-cigarettes (Dobbs et al, 2016), schools have been encouraged to include more education about these emerging products within their tobacco prevention education (Anand et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The interventions of students, who are close in age, seem to be particularly effective with adolescents on subjects such as alcohol, drug and tobacco consumption. In experiments reported by Brinker et al medical student interventions appeared to be effective in primary prevention of tobacco use, and in promoting smoking cessation [ 20 22 ]. In France, a health service study conducted by medical students reported positive effects in terms of knowledge, skills and behaviour on pupils and positive effects on the students themselves [ 23 ].…”
Section: Discussionmentioning
confidence: 99%